Microclimate relationships of intraspecific trait variation in sub‐Arctic plants. Issue 12 (7th September 2022) - Kemppinen, Julia; Niittynen, Pekka
Abstract : Within‐species trait variation is a substantial part of plant functional diversity. However, this intraspecific trait variation (ITV) is rarely investigated in relation to a key characteristic of the Arctic and alpine ecosystems: fine‐scale microclimatic heterogeneity. Here, we quantified the influence of microclimate (soil moisture, snow and local temperatures) on plant functional traits, specifically on ITV. We focused on six widespread northern latitude vascular plant species, and measured four traits: plant height, leaf area, leaf dry matter content (LDMC) and specific leaf area (SLA). We related ITV to field and remotely sensed microclimate data from 150 study plots within six study grids. The grids were located within a 76‐m altitudinal belt in three environments: the tundra, tundra–forest ecotone and mountain birch forest in Kilpisjärvi, northwestern Finland. We compared the range of trait values between this local trait dataset (n = 5493) and global trait databases (n = 10 383). We found that information in the local dataset covers a relatively large portion of the trait ranges in global databases. The proportion varies among traits and species; the largest portion was 74% for variation in leaf area of Vaccinium uliginosum, and the lowest was 19% for LDMC of Betula nana . We found that ITV in height was mostly related to local temperatures, whereas SLA and LDMC were more related to soil moisture and snow conditions. However, species showed contrasting relationships with the microclimate drivers. We conclude that microclimate profoundly shapes ITV in northern latitude plants and that even a very compact geographic area can contain a large amount of ITV. The influence of the microclimatic conditions varies among functional traits and species, which indicates that plastic response or adaptive potential of the species to climate change may also vary across species, but that necessary variation may often be present within local plant populations.